Atypical Craniosynostosis with Torticollis and Neurological Symptoms: A Rhombencephalosynapsis Sequence. (6th December 2009) - Koljonen, Virve; Leikola, Junnu; Valanne, Leena; Hukki, Jyri
Abstract : Purpose . We describe a case of 3-year-old girl with rhombencephalosynapsis, a rare cerebellar anomaly. Patient . A 3-year-old girl was admitted to our hospital due to congenital torticollis and asymmetry of face, skull and trunk. Craniosynostosis was suspected due to abnormal head shape. 3D-CT revealed closure of the sagittal suture without scaphocephalic skull. Due to atypical craniosynostosis with neurological symptoms, brain-MRI was performed revealing rhombencephalosynapsis. Results . Our patient presented with atypical craniosynostosis and balance problems, not typical for scaphocephaly. Operative treatment for craniosynotosis was not carried out because the cause of the problems was the cerebellum instead of the brain. Conclusions . Therefore, we conclude that patients with atypical craniosynostosis should be examined with brain-MRI to exclude the intracranial malformations, which 3D-CT does not reveal. Without brain-MRI, decision (not) to perform surgery could have been different.